Dynamic capabilities for stakeholder management - Valle, Carine Dalla (2022)
Companies can use a wide range of dynamic capabilities to improve their performance in a dynamic and competitive environment. This study aims to analyze which dynamic capabilities are related to stakeholder management. A systematic review was carried out on articles published in the Web of Science database. The results contribute to management literature and practice by indicating eleven dynamic capabilities for stakeholder management. According to the literature, these capacities are conceptualized, and routines and ways of developing are presented. The second contribution of the research refers to discussing which capabilities have a greater or lesser potential for creating a competitive advantage. Finally, this research proposes a model for analyzing the influence of dynamic capabilities on each other and their relationship with the competitive advantage of companies.